Development of Critical Thinking Test Instruments with Problem Solving Context on The Salt Hydrolysis Material - Budi Susetyo; Wiwi Siswaningsih*; Fizky Rizki Oktavi (Universitas Syiah Kuala, 2021)
The assessment tools must be developed to measure the competencies in 21st century skills, such as critical thinking and problem-solving. Critical thinking is seen as a prerequisite for problem-solving abilities. Therefore, this study aims to produce critical thinking test with problem-solving context on the salt hydrolysis material, also measure students’ mastery of the critical thinkings sub-indicators and problem-solving indicators. The research method used the development and validation. Participants involved in the test were 42 students of class XI who had studied salt hydrolysis at a high school in Bandung. The product from this research is critical thinking skills test instrument in the context of problem-solving as many as 10 multiple choice with an open reason on the salt hydrolysis material. Based on results of test quality, the developed test has good and decent criteria. The instruments declared valid based on the content validity at the CVR value and the empirical validity on Pearson's product-moment correlation coefficient, and reliable with Cronbach Alpha value of 0.823. Criteria for empirical validity and reliability test as a whole are included in high and very high. The results analysis quality of the items as a whole have medium difficulty level, very good distinguishing power, and good distractor effectiveness. The results of level student mastery in the critical thinkings sub-indicators and problem-solving indicators that are most mastered are to express problems and mention facts related to the problems. Meanwhile, the least mastered are drawing conclusions according to facts and checking the feasibility of the solutions made.